GESTURES IN ENGLISH LANGUAGE TEACHING - Rahmi Rahmi (Pedagogik : Jurnal Ilmiah Pendidikan dan Pembelajaran Fakultas Tarbiyah Universitas Muhammadiyah Aceh, 2016)
Human beings interact not only with verbal communication, but also nonverbal communication. Nonverbal communication is very important in interactional process and one of its forms is gestures. Because gestures and language affect each other, gesture issues have been studied as an essential part in second and foreign language classroom. It is because gestures can help learners to comprehend the language and enjoy the learning activities.